(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In Uzbekistan’s transitioning economy, small and medium-sized enterprises (SMEs) play a pivotal role in driving growth, employment, and innovation. However, many SMEs lack the methodological frameworks to re-engineer their business processes when adopting innovative technologies. This study examines the factors compelling SMEs in Uzbekistan to undertake business process reengineering (BPR), analyzes the current state of BPR implementation, and proposes a structured framework for effective re-engineering in these enterprises.